2012
DOI: 10.1242/jcs.089367
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of actin microfilaments by human MICAL proteins

Abstract: SummaryThe Drosophila melanogaster MICAL protein is essential for the neuronal growth cone machinery that functions through plexin-and semaphorin-mediated axonal signaling. Drosophila MICAL is also involved in regulating myofilament organization and synaptic structures, and serves as an actin disassembly factor downstream of plexin-mediated axonal repulsion. In mammalian cells there are three known isoforms, MICAL1, MICAL2 and MICAL3, as well as the MICAL-like proteins MICAL-L1 and MICAL-L2, but little is know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(136 citation statements)
references
References 34 publications
(60 reference statements)
11
125
0
Order By: Relevance
“…Refs. [43][44][45]. For instance, a transcript variant (TXNRD1_v3) of the selenoprotein thioredoxin reductase 1 encodes an atypical N-terminal Grx domain.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [43][44][45]. For instance, a transcript variant (TXNRD1_v3) of the selenoprotein thioredoxin reductase 1 encodes an atypical N-terminal Grx domain.…”
Section: Discussionmentioning
confidence: 99%
“…They are widely expressed in nervous system and other tissues, including endothelial cells and cancer cells such as melanoma and HeLa cells 4, 5, 6, 7. Although MICAL family is identified as MICAL (1‐3) and MICAL‐like (‐L1, ‐L2) forms in mammals, its main functions were studied mostly in Drosophila 1, 3, 8.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have demonstrated that the full-length MICAL1 is catalytically inactive as it adopts an auto-inhibitory state in the absence of stimuli (Giridharan et al, 2012b;Schmidt et al, 2008). The N-and C-terminal regions of the protein have been shown to physically interact and this likely inhibits the enzymatic activity (Schmidt et al, 2008).…”
Section: Activation Of Mical1mentioning
confidence: 99%
“…Uncontrolled activation of MICAL family members leads to almost complete depolymerization of all F-actin pools in cells (Giridharan et al, 2012b;Grigoriev et al, 2011;Hung et al, 2010), implying that MICAL-mediated enzymatic activity and localization must be tightly regulated. In this section, we discuss the most recent findings we and other have obtained with regard to the localization and activation of MICALs, in particular the emerging roles of Rab GTPases in both processes.…”
Section: Mechanisms Of Recruitment and Activation Of Mical1 During Cementioning
confidence: 99%
See 1 more Smart Citation